2021
DOI: 10.1021/acssuschemeng.1c06784
|View full text |Cite
|
Sign up to set email alerts
|

Vegetable Oils as Sustainable Inks for Additive Manufacturing: A Comparative Study

Abstract: The use of biobased materials in additive manufacturing is arising as a promising approach to modernize the polymer industry reducing its environmental impact. Herein, novel sustainable formulations are developed for digital light processing (DLP) using five vegetable oilssunflower, canola, soybean, olive, and sesame oilas feedstock. These vegetable oils are successfully modified incorporating photopolymerizable groups, i.e., acrylates, enabling printability. The oil-based formulations consisting of a functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 41 publications
(70 reference statements)
0
24
0
Order By: Relevance
“…29 A 3D printed canola oil acrylate, which contained the highest number of acrylate groups per molecule of the oils studied, showed the highest tensile modulus, followed by the state-of-the-art soybean oil-based resin. 30 Moreover, an excellent shape memory effect is achieved with 3D printed AESO-based resin, 31 while 3D printed UV curable bio-based vitrimer materials possess self-healing properties. 32 Recently, novel heat-resistant 3D printed acrylates from glycidyl methacrylate, succinic acid, and itaconic acid were obtained, showing superior properties to commercial high-temperature-resistant resins (Carbon CE221, Formlabs High Temp).…”
Section: Introductionmentioning
confidence: 99%
“…29 A 3D printed canola oil acrylate, which contained the highest number of acrylate groups per molecule of the oils studied, showed the highest tensile modulus, followed by the state-of-the-art soybean oil-based resin. 30 Moreover, an excellent shape memory effect is achieved with 3D printed AESO-based resin, 31 while 3D printed UV curable bio-based vitrimer materials possess self-healing properties. 32 Recently, novel heat-resistant 3D printed acrylates from glycidyl methacrylate, succinic acid, and itaconic acid were obtained, showing superior properties to commercial high-temperature-resistant resins (Carbon CE221, Formlabs High Temp).…”
Section: Introductionmentioning
confidence: 99%
“…Vasquez-Martels et al reported some limited applications of VO (sunflower, canola, soybean, olive, and sesame functionalized with acrylates) for SLA/DLP. 7 aforementioned work, compositions based on canola oil had the highest modulus (14 MPa) followed by sunflower and soybean oil (SO) (10 MPa). SO (the second most-produced VO in the world 8 ) has been successfully commercialized in the form of acrylated epoxidized soybean oil (AESO), which is typically found in various 3D printable resin compositions.…”
Section: ■ Introductionmentioning
confidence: 87%
“…Therefore, VO-based resins have been investigated for UV-assisted 3D printing technologies. Vasquez-Martels et al reported some limited applications of VO (sunflower, canola, soybean, olive, and sesame functionalized with acrylates) for SLA/DLP . So far, VO-based resins have shown printing accuracy comparable to those of expensive, high-resolution commercial resins.…”
Section: Introductionmentioning
confidence: 99%
“…The resolution of the printed objects was determined by printing custom designed specimens bearing engraved lines with widths varying between 1000 μm, 500 μm, 250 μm, and 100 μm. 45 Then the samples were examined by optical microscope (Zeiss AXIO Scope A1). All the features were clearly perceptible and retained the same shape, with ≈ 10 % isotropic shrinkage after the development process related to solvent evaporation (Figure S5).…”
Section: Printing Parameters and Optimizationmentioning
confidence: 99%